1987
DOI: 10.1530/acta.0.1160350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexamethasone on ovarian activity in rats

Abstract: Rats with 5-day ovarian cycles were treated with dexamethasone (0.025 to 0.4 mg per rat per day) to examine its effects on ovarian activity. All doses of dexamethasone markedly suppressed endogenous secretion of ACTH as evidenced by decrease in weight of the adrenal glands after 7-23 days of treatment. Treatment with 0.4 mg of dexamethasone from the day of ovulation appeared to induce pseudopregnancy in more than 90% of the rats studied: pseudopregnancies lasted for 14-22 days. Induction of pseudopregnancy occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…These data are consistent with previous reports that DEX [22,25] and triamcinolone acetonide, another synthetic glucocorticoid, can enhance ovulation [27]. We further demonstrated that DEX treatment yielded a 1½ to 2-fold increase in litter size.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data are consistent with previous reports that DEX [22,25] and triamcinolone acetonide, another synthetic glucocorticoid, can enhance ovulation [27]. We further demonstrated that DEX treatment yielded a 1½ to 2-fold increase in litter size.…”
Section: Discussionsupporting
confidence: 93%
“…This regimen normally results in ovulation around midnight of experiment day 3. The number of follicles that mature and release oocytes under this eCG/hCG dosage protocol is similar to normally cycling rats [11,12,22], i.e. we did not intend to induce superovulation.…”
Section: Animals and Treatmentsmentioning
confidence: 71%
See 1 more Smart Citation
“…X70. trous cycle, were also consistent with effects described for synthetic glucocorticosteroids in the dog (23). Inhibition of ovulation due to glucocorticosteroid-induced suppression of luteinizing hormone (LH) release (ie, preovulatory LH surge) has been described for rodents and women (4,12,13,38). Inhibition of the preovulatory LH surge in female rabbits has also been demonstrated with medroxyprogesterone acetate (31).…”
Section: Methodssupporting
confidence: 75%
“…As TPA is thought to play an important role in ovulation, this effect could have important physiological relevance. This finding may also explain that dexamethasone treatment on proestrus, in some cases resulted in an unexpectedly large number of eggs per ovulating animal [17,18]. …”
Section: Physiological Role Of Adrenal Steroids In Reproductionmentioning
confidence: 88%